The international energy agency in global energy governance - FLORINI, Ann (Institutional Knowledge at Singapore Management University, 2011)
The International Energy Agency (IEA) is the organization that, despite its constrained membership, is as close as the world currently comes to a global focal point on the key energy governance arenas. Although when the IEA was established in the 1970s it had the specific and limited purpose of enabling the world's leading oil consumers to undertake collective action in response to oil supply shocks, it now finds itself at the center of many of the key developments in global energy governance. Its evolution and current challenges reflect the key themes of this special issue: the competition between state and market, the emergence of multipolarity, the particular growing importance of Asia and the rise of climate change on the agenda of key tasks needing governance. The article focuses on where the agency now fits in the larger global energy governance panoply. © 2011 London School of Economics and Political Science and John Wiley & Sons Ltd.